Predicting Psychological Needs and Well-Being of Individuals Engaging in Weight Management: The Role of Important Others - Ng, J.; Ntoumanis, Nikos; Thøgersen-Ntoumani, Cecilie; Stott, K.; Hindle, L. (Wiley-Blackwell Publishing, 2013)
Background: Using the self-determination theory (SDT) framework, we examined how significant others might support or thwart psychological needs of people with weight management goals, and in turn might affect their psychological well-being and weight control behaviors. Design: Longitudinal design with three sets of questionnaires administered over a 6-month period. Methods: One hundred and fifty-six eligible participants (age = 31.01 ± 13.21 years) were asked to complete questionnaires of SDT-based constructs, weight management behaviors, and psychological well-being. Hypotheses were tested using Bayesian path analysis. Results: Perceived autonomy support from significant others was related to psychological need satisfaction, while controlling behaviors by others were associated with need thwarting. In turn, need satisfaction was associated with some beneficial outcomes such as life satisfaction, and need thwarting was related to some maladaptive outcomes such as higher levels of depressive symptoms and increases in unhealthy diet behaviors. Conclusions: Our findings indicate that the quality of interactions between individuals engaged in weight management and their significant others matters in terms of predicting the psychological needs and well-being of the former.